2010
DOI: 10.1136/bmj.c6624
|View full text |Cite
|
Sign up to set email alerts
|

Derivation, validation, and evaluation of a new QRISK model to estimate lifetime risk of cardiovascular disease: cohort study using QResearch database

Abstract: Objective To develop, validate, and evaluate a new QRISK model to estimate lifetime risk of cardiovascular disease.Design Prospective cohort study with routinely collected data from general practice. Cox proportional hazards models in the derivation cohort to derive risk equations accounting for competing risks. Measures of calibration and discrimination in the validation cohort.Setting 563 general practices in England and Wales contributing to the QResearch database.Subjects Patients aged 30–84 years who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
235
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(247 citation statements)
references
References 37 publications
7
235
1
4
Order By: Relevance
“…In the primary prevention setting, lifetime estimates have been shown to identify patients most likely to benefit from treatment at a much earlier age 11, 13, 14, 17, 32, 33, 34. The present study demonstrates that this likely also applies to patients with established cardiovascular disease.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In the primary prevention setting, lifetime estimates have been shown to identify patients most likely to benefit from treatment at a much earlier age 11, 13, 14, 17, 32, 33, 34. The present study demonstrates that this likely also applies to patients with established cardiovascular disease.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, recent studies have shown that estimating cardiovascular prognosis from a lifetime perspective may have some advantages over 10‐year risk estimation, including a potentially better selection of patients for preventive treatment by accounting for remaining life expectancy and competing events 11, 12, 13, 14, 15, 16, 17. For example, the QRISK lifetime model in the primary prevention setting identifies patients with an unfavorable prognosis at a much younger age than the traditional 10‐year risk approach 11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient's risk of developing CVD is then calculated using a CVD risk score calculator, which may include the Joint British Societies (JBS) 12 calculator or the QRISK ® 2 score. 13 During the period of this trial, the JBS calculator was mandated by the Health Check programme in the study area. The cardiovascular risk assessment implemented as part of the health check is used to inform graded intervention.…”
mentioning
confidence: 99%
“…A rizikó megítélésében igen hasznos a SCOREtáblázat [4], azonban ez is csak 65 éves korig ad információt. Egyes validált rizikóbecslő módszerek idősebb életkorban is alkalmazhatóak (például QRISK-score) [5], azonban ezek használata a hazai gyakorlatban egyelőre nem terjedt el. Cukorbetegekben primer prevencióban is javasolt lehet az ASA használata (elsősorban 50 év feletti férfi ak és 60 év feletti nők esetén, ha legalább még egy cardiovascularis kockázati tényező fennáll), azonban az ASA primer cardiovascularis prevencióban történő ajánlása az évek során sokat változott [6].…”
Section: Az Nsaid-ok éS Az Aszpirin Együttes Használataunclassified